2017
DOI: 10.1007/s11837-017-2350-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Microstructure and Texture in AZ31 Alloy Subjected to Gas Forming

Abstract: In this study, AZ31 sheets were subjected to gas forming using a stepped geometry die and employing two different temperatures (400°C and 450°C) and exposure times (60 s and 120 s). Microstructural examinations revealed that the density of the mechanical twins may be taken as indicative of the progress of recrystallization together with the relative grain size. Although gas forming was successfully applied, the severe residual texture inherited from the initial materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Before applying the gas pressure, the die and the blank holder were both heated to a temperature of 450 ºC by two ceramic band heaters. According to recent studies by Sorgente et al [5] and Kaya et al [6] this temperature represents a valuable compromise between the forming time, microstructure and formability. The 1.2 mm thick AZ31B sheet was then clamped between the die and the blank holder with a force enough to seal the chamber between the blank holder and the sheet.…”
Section: Methodsmentioning
confidence: 99%
“…Before applying the gas pressure, the die and the blank holder were both heated to a temperature of 450 ºC by two ceramic band heaters. According to recent studies by Sorgente et al [5] and Kaya et al [6] this temperature represents a valuable compromise between the forming time, microstructure and formability. The 1.2 mm thick AZ31B sheet was then clamped between the die and the blank holder with a force enough to seal the chamber between the blank holder and the sheet.…”
Section: Methodsmentioning
confidence: 99%
“…Before applying the gas pressure, the die and the blank holder were both heated to a temperature of 450 • C by a ceramic band heater. According to recent studies by Sorgente et al [12] and Kaya et al [13], this temperature represents a valuable compromise between forming times, microstructure and formability. The 1.2 mm thick AZ31B sheet was then clamped between the die and the blank holder with force enough to seal the chamber between the blank holder and the sheet.…”
Section: Mgmentioning
confidence: 99%
“…Gas forming at elevated temperature, sometimes reported as hot metal gas forming, is one of the promising manufacturing processes for Mg alloys [2]. AZ31 alloy is among a limited number of commercialized magnesium alloys that has been largely adopted [3] and proved to have a very good formability between 400°C and 450°C [4]. Kim et al [5] reported that in the superplastic forming process, due to a significant grain coarsening of the AZ31 Mg alloy, a comparison between alloys with different initial grain sizes could be an effort in vane.…”
Section: Introductionmentioning
confidence: 99%